ANALYSIS OF POSTURAL STABILITY OF YOUNG ADULTS IN THE PRESENCE AND MOMENTARY ABSENCE OF VISION (Fiep Bulletin - online, 2011)
The aim of this study was to analyze the influence of momentary deprivation of vision on the postural orthostatic balance of healthy young individuals, based on the oscillation of the center of pressure. Four subjects, one male and three females, mean age 24 ± 3.4 years, body weight 666.97 ± 104.18 N, and height 1.68 ± 0.07 meters participated in this study. Data was collected on a force platform under two conditions; eyes open and eyes closed. The test was repeated three times, 60 seconds for each condition. Variables included force and moment of force, axes X, Y, Z. Deprivation of vision caused changes in trajectory, velocity, and displacement of the center of pressure, causing higher center of gravity oscillation.
Keywords: Momentary absence of vision; Postural control; Posturography.